Differentiated Visions: How Ontario Universities See and Represent Their Futures - Buzzelli, Michael; Songsore, Emmanuel (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
This paper is concerned with long term strategic planning in higher education and focuses on Ontario’s strategic mandate agreement (SMA) sector planning framework. In 2012, the province initiated its new SMA planning process by requiring all higher education institutions to propose their own strategies for their academic visions, missions, and objectives. The proposals submitted by Ontario’s universities furnish the empirical content of this paper: a historically unique, comprehensive and comparable set of documents capturing institutions’ self-understanding and plans for their respective futures. Using concepts from organizational theory, content analysis of universities’ SMA proposals reveals divergent strategies, both in terms of institutional administrative responsiveness to the SMA process as well as the academic (i.e., education and scholarship) content of the submissions. In addition, two further sub-themes are analysed: proposals for experiential learning and so-called town-gown connections. Both themes also reveal very different visions amongst institutions. In general, the proposals appear to be independent of institution type and community size/location. Setting the stage for future research, the paper concludes with policy discussion of: (i) the possibilities for institutional diversity in the context of policy discourses on institutional differentiation; (ii) implications for system planning given the structure and process of Ontario’s ongoing SMA framework.